Analysis of a Deep Learning Approach Based on Cultural Values in Pancasila Education at Elementary Schools in Simpang Mamplam District - Insanil Qadri; Najmuddin Najmuddin; Sari Rizki; Machfud Machfud (Sakura Digital Nusantara, 2026)
This study was motivated by the continued dominance of teacher-centered learning and the limited integration of local cultural values into Pancasila Education in elementary schools. It aimed to examine teachers' understanding of a deep learning approach based on local cultural values, analyze its implementation, and identify the supporting and inhibiting factors in elementary schools in Simpang Mamplam District. This study employed a descriptive qualitative approach involving five elementary schools. Data were collected through classroom observations, semi-structured interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings showed that teachers had a good understanding of the deep learning approach and successfully integrated Acehnese traditions, gotong royong, religious values, folklore, and community activities into Pancasila Education, creating more contextual, meaningful, and student-centered learning. Classroom observations indicated an average implementation score of 97.2%, categorized as excellent. The main supporting factors were the strong local cultural environment, support from school principals, parents, and school committees, and students' enthusiasm. Meanwhile, limited digital learning media, time constraints, and differences in students' learning abilities became the primary challenges. Overall, integrating local cultural values into a deep learning approach enhances the quality of Pancasila Education by promoting meaningful learning and strengthening students' character. This study contributes to the literature by proposing a contextual learning model that integrates deep learning with local cultural values and provides practical guidance for implementing culturally responsive learning within the Independent Curriculum.